Expression and Implication of Clusterin in Left Ventricular Remodeling After Myocardial Infarction. (June 2018) - Turkieh, Annie; Fertin, Marie; Bouvet, Marion; Mulder, Paul; Drobecq, Hervé; Lemesle, Gilles; Lamblin, Nicolas; de Groote, Pascal; Porouchani, Sina; Chwastyniak, Maggy; Beseme, Olivia; Amouyel, Philippe; et al.
Abstract : Background: Left ventricular remodeling (LVR) after myocardial infarction is associated with an increased risk of heart failure and death. In spite of a modern therapeutic approach, LVR remains relatively frequent and difficult to predict in clinical practice. Our aim was to identify new biomarkers of LVR and understand their involvement in its development. Methods and Results: Proteomic analysis of plasma from the REVE-2 study (Remodelage Ventriculaire)—a study dedicated to the analysis of LVR which included 246 patients after a first anterior myocardial infarction—identified increased plasma levels of CLU (clusterin) in patients with high LVR. We used a rat model of myocardial infarction to analyze CLU expression in the LV and found a significant increase that was correlated with LVR parameters. We found increased CLU expression and secretion in primary cultures of rat neonate cardiomyocytes hypertrophied by isoproterenol. Silencing of CLU in hypertrophied neonate cardiomyocytes induced a significant decrease in cell size, ANP (atrial natriuretic peptide), and BNP (B-type natriuretic peptide) expression, associated with a decreased ERK (extracellular signal-regulated kinase) 1/2 activity, suggesting a prohypertrophic role of CLU. We then confirmed a significant increase of both intracellular p-CLU (precursor form of CLU) and m-CLU (mature form of CLU) in failing human hearts. Finally, the circulating levels of CLU (secreted form) were increased in patients with chronic heart failure who died from cardiovascular cause during a 3-year follow-up (n=99) compared with survivors (n=99). Conclusions: Our results show for the first time that plasma CLU levels are associated with LVR post–myocardial infarction, have in part a cardiac origin, and are a predictor of early death in heart failure patients. Abstract : Supplemental Digital Content is available in the text.